Living in the Present with Anapanasati - Krongcheep, Siriporn; Somphol, Phurichetd; Ponsen, Kitsuchin (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 13 No 1 (2021): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This article is intended to, 1) to study the meaning of Anapanasati 2) to study how to grow Anapanasati in the Tripitaka 3) to study the development of Anapanasati along the Visuddhimagga from studying the meaning of Anapanasati, it can be seen that it defines the inhalation and exhalation knowing that he was breathing in and exhaling until the mind is calm and still in the breath it can cut anxiety highs making him happy in every position how to grow Anapanasati in the Tripitaka practician be an educator determine how to inhale and exhale with persistence conscious eliminate apical and sorrow the development of Anapanasati along the Visuddhimagga is the selection of happiness that is suitable for prayer because the mind is accustomed to running into various emotions external because still attached to the picture, sound, smell, taste difficult to make this happen for that reason sound is a hindrance to contemplation in the forest it is easy to make contemplation born with the development of Anapanasati and make meditation as a base living Vipassana, considering the body until finally attainment of Arhatship.